2018
DOI: 10.1016/j.molcel.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

A Muscle-Specific Enhancer RNA Mediates Cohesin Recruitment and Regulates Transcription In trans

Abstract: The enhancer regions of the myogenic master regulator MyoD give rise to at least two enhancer RNAs. Core enhancer eRNA (eRNA) regulates transcription of the adjacent MyoD gene, whereas eRNA affects expression of Myogenin in trans. We found thateRNA is recruited at the Myogenin locus, where it colocalizes with Myogenin nascent transcripts. eRNA associates with the cohesin complex, and this association correlates with its transactivating properties. Despite being expressed in undifferentiated cells, cohesin is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
172
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(181 citation statements)
references
References 94 publications
(135 reference statements)
9
172
0
Order By: Relevance
“…There may also be a role for noncoding RNA in enhancer-promoter interactions 25,26,[78][79][80] . Notably, whilst mRNA has been shown to direct the formation of phase condensate compartments in the cytoplasm 81 and eRNAs have been proposed to play a similar role in the formation of enhancer-promoter complexes 25,26 our results following dissolution of phase condensates with hexanediol treatment argue that these interactions are not sufficient for maintaining contact at many genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There may also be a role for noncoding RNA in enhancer-promoter interactions 25,26,[78][79][80] . Notably, whilst mRNA has been shown to direct the formation of phase condensate compartments in the cytoplasm 81 and eRNAs have been proposed to play a similar role in the formation of enhancer-promoter complexes 25,26 our results following dissolution of phase condensates with hexanediol treatment argue that these interactions are not sufficient for maintaining contact at many genes.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, whilst mRNA has been shown to direct the formation of phase condensate compartments in the cytoplasm 81 and eRNAs have been proposed to play a similar role in the formation of enhancer-promoter complexes 25,26 our results following dissolution of phase condensates with hexanediol treatment argue that these interactions are not sufficient for maintaining contact at many genes. However, RNA may play other roles in directing enhancer-promoter interactions, for example by recruitment of cohesin 79,80 .…”
Section: Discussionmentioning
confidence: 99%
“…This leads to suboptimal polyadenylation, RNA exosome intervention, and rapid degradation (Ntini et al, 2013). Such a model would explain why longer eRNAs tend to be polyadenylated, and is supported by studies that have examined specific eRNA length, polyadenylation, and degradation (Schaukowitch et al, 2014;Tsai et al, 2018). Additional studies have found that the same eRNAs can be detected through RT-PCR using oligo-dT or random hexamer primers, with the oligo-dT primers generally providing weaker signal (Hah et al, 2013;Pulakanti et al, 2013).…”
Section: Structure and Heterogeneity Of Ernamentioning
confidence: 94%
“…We also tested the interaction of endogenous RPB1, RPRD1A and RPRD1B proteins in NIH3T3 cells treated with lysine deacetylase (KDAC) inhibitors. KDAC inhibitor treatment induced robust hyperacetylation of endogenous RPB1 in input material as tested with an antibody specific for K7ac (Schroder et al, 2013), but did not change unmodified Pol II protein levels as measured with the 8WG16 antibody, which correlate with total Pol II levels (Tsai et al, 2018;Vian et al, 2018) (Figure 1E). After pulldown of endogenous Pol II, more RPRD1A and RPRD1B proteins were recovered when cells were treated with KDAC inhibitors as compared to vehicle-treated cells, confirming positive regulation of the RPB1:RPRD interaction by acetylation ( Figure 1E, F).…”
Section: Preferential Binding Of Rprd Proteins To Acetylated Rpb1mentioning
confidence: 93%